Improving safety and availability of complex systems by using an integrated design approach in development. Issue 4 (31st January 2012) - Bachmann, Volker; Messnarz, Richard; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
ABSTRACT Within the last 5 years the need for a system development and a process that describes this development became more and more obvious. The number of software and electronic engineers rose even in companies that were traditionally working in the field of pure mechanics. The ISO standard 15504 was consequently expanded from the software to the system. Nevertheless, even 5 years after this change, there is nearly no subsystem mechanics completely described in the same tool as the subsystems electronics and software. This break within the tool chain is the tip of an iceberg reaching all the way down to the lived processes in development. This paper tries to give a solution that was worked out in a group of integrated designers that developed a program for the European Certification and Qualification Association. It shows an example that was tested in an industry project to reach level two, according to the Automotive SPICE standard, on system level in a customer assessment. It shows how to bring together standards that are used in electronics, software, and mechanics to find an integrated design approach to improve safety and availability of systems composed of these parts. Namely, this is the IEC 61508 asking for a risk analysis, which again finds entrance into the failure mode and effects analysis (FMEA) that is a commonly known tool in mechanical development. The FMEA again has an interface to the ISO 15504, which is described here as well. An integrated design is the outcome of this process by using the tools mentioned and bringing them together properly. Copyright © 2012 John Wiley & Sons, Ltd.